2015
DOI: 10.1080/02827581.2015.1018936
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of genetic gain and diversity under various genetic thinning scenarios in a breeding seed orchard ofQuercus acutissima

Abstract: Genetic gain and diversity were estimated based on three simulated thinning scenarios at various thinning intensities in a breeding seed orchard of Quercus acutissima. The seed orchard was composed of 32 families with 744 individual trees with volume at age 15. The three thinning scenarios were individual thinning (IT) which thinning was based on the individual performance, family thinning (FT) with the removal of inferior families regardless of individual performance, and family + within family thinning (FWF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Previous reviews of North American oaks (mainly Q. alba , Q. rubra , Q. falcata and Q. pagoda ) (Kriebel, ) and European oaks (mainly Q. petraea and Q. robur ) (Kleinschmit, ) highlighted the existence of already extremely variable phenotypes within and between progenies raised in common gardens in terms of height and diameter growth, crown form and phenology. Similar outcomes were also observed more recently in Asian species for growth (in Q. acutissima (Na et al , ) and Q. serrata (Kang et al , )). Within the context of environmental change, attention has shifted towards fitness‐related traits, such as phenology, resistance to biotic and abiotic stresses, and reproduction (Ramirez‐Valiente et al , ; Brendel et al , ).…”
Section: Microevolution In Oakssupporting
confidence: 88%
“…Previous reviews of North American oaks (mainly Q. alba , Q. rubra , Q. falcata and Q. pagoda ) (Kriebel, ) and European oaks (mainly Q. petraea and Q. robur ) (Kleinschmit, ) highlighted the existence of already extremely variable phenotypes within and between progenies raised in common gardens in terms of height and diameter growth, crown form and phenology. Similar outcomes were also observed more recently in Asian species for growth (in Q. acutissima (Na et al , ) and Q. serrata (Kang et al , )). Within the context of environmental change, attention has shifted towards fitness‐related traits, such as phenology, resistance to biotic and abiotic stresses, and reproduction (Ramirez‐Valiente et al , ; Brendel et al , ).…”
Section: Microevolution In Oakssupporting
confidence: 88%
“…Both genetic gain and diversity depend on the variation of reproductive success in the CSO, synchrony in reproductive phenology, pollen quality and contamination, self-fertilization rates, seed germination, and other factors. Many studies have shown that there can be a considerable gulf between expectations and reality (Askew 1988;Burczyk et al 1997;Edwards and ElKassaby 1996;Funda et al 2009;Gomory et al 2003;Hansen 2008;Kang and Lindgren 1998;Machanska et al 2013;Matziris 1994;Na et al 2015), making it difficult to predict genetic quality. Moreover, the selfing rate in the CSO and inbreeding depression were not taken into account in the estimation of genetic gain and diversity.…”
Section: Genetic Gain and Diversity In Commercial Seed Orchardsmentioning
confidence: 99%
“…Most of the clones (selected from dry locations) were superior to native provenance seed at a dry site, whereas the number of superior clones decreased in an intermediate-rainfall site, and most clones were inferior to seed sources at a high-rainfall site (Varghese et al, 2008). Since genetic diversity is essential for survival and adaptability of crop plants in diverse sites (Rao and Hodgkin, 2002) strategies to maximise gain in breeding orchards will result in loss of genetic diversity (Na et al, 2015).…”
Section: Trade-off Between Genetic Diversity and Phenotypic Traitsmentioning
confidence: 99%